Early warning early action for the banking solvency risk in the COVID-19 pandemic era: A case study of Indonesia - Taufiq Hidayat; Dian Masyita; Sulaeman Rahman Nidar; Fauzan Ahmad; Muhammad Adrissa Nur Syarif (Economies, 2022)
The COVID-19 pandemic has affected people's lives and increased the banking solvency risk. This research aimed to build an early warning and early action simulation model to mitigate the solvency risk using the system dynamics methodology and the Powersim Studio 10© software. The addition of an early action simulation updates the existing early warning model. Through this model, the effect of policy design and options on potential solvency risks is known before implementation. The trials conducted at Bank BRI (BBRI) and Bank Mandiri (BMRI) showed that the model had the ability to provide an early warning of the potential increase in bank solvency risk when the loan restructuring policy is revoked. It also simulates the effectiveness of management's policy options to mitigate these risks. This research used publicly accessible banking data and analysis. Bank management could also take advantage of this model through a self-stimulation facility developed in this study to accommodate their needs using the internal data.
Keywords: 330; banking sector; corporate insolvency; COVID-19 outbreak; early warning early action; loan restructuring policy; simulation; system dynamics